2016
DOI: 10.4049/jimmunol.1502383
|View full text |Cite
|
Sign up to set email alerts
|

The ETS Family Transcription Factors Etv5 and PU.1 Function in Parallel To Promote Th9 Cell Development

Abstract: The IL-9-secreting Th9 subset of CD4 T helper cells develop in response to an environment containing IL-4 and TGFβ, promoting allergic disease, autoimmunity, and resistance to pathogens. We previously identified a requirement for the ETS family transcription factor PU.1 in Th9 development. In this report we demonstrate that the ETS transcription factor ETV5 promotes IL-9 production in Th9 cells by binding and recruiting histone acetyltransferases to the Il9 locus at sites distinct from PU.1. In cells that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…IL-9 production was decreased in the absence of ETV5, and ectopic expression of ETV5 increased IL-9 production [56]. ETV5, which also promotes IL-17A/F production in Th17 cells [57], significantly bound to the Il9 gene at regions distinct from the promoter that bound PU.1 [56](Fig. 2).…”
Section: The Ets Family: Pu1 and Etv5mentioning
confidence: 99%
See 2 more Smart Citations
“…IL-9 production was decreased in the absence of ETV5, and ectopic expression of ETV5 increased IL-9 production [56]. ETV5, which also promotes IL-17A/F production in Th17 cells [57], significantly bound to the Il9 gene at regions distinct from the promoter that bound PU.1 [56](Fig. 2).…”
Section: The Ets Family: Pu1 and Etv5mentioning
confidence: 99%
“…2). Binding of the HAT p300 was dependent on ETV5, but Gcn5 binding was normal in the absence of ETV5 [56]. Th9 cells that were doubly deficient in PU.1 and ETV5 had less IL-9 production than Th9 cells from either single deficient strain.…”
Section: The Ets Family: Pu1 and Etv5mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, those that can engage the Il9 promoter region include PU.1, IRF1, IRF4, STAT5, STAT6, NFAT, GATA1, GATA3, Smads, Etv5 and Notch, as well as NF-κB, BATF, AP-1[9]. Etv5 can also bind the CNS0 and CNS2 regions and mediate chromatin remodeling by recruiting the histone acetyltransferase p300 [53]. TCR stimulation, polarizing cytokines, and costimulatory molecules, especially those in the TNFR superfamily, are all involved in the expression of such transcription factors.…”
Section: Inducing and Defining Th9 Cellsmentioning
confidence: 99%
“…A recent study identified a demand of ETS transcription factor ETS variant 5 (ETV5) to augment IL-9+ Th9 cells with an enrichment of histone acetyltransferases (HATs) within the IL-9 gene promoter. In vitro study showed that a reduction of p300 in the absence of ETV5, accompanied by low level of histone H3 acetylation and H4K16 acetylation enriched in the Il9 promoter [63]. …”
Section: Microrna Transcriptsmentioning
confidence: 99%